1991
DOI: 10.1177/073346489101000107
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Home and Community-Based Services

Abstract: The quality of long-term home health services is particularly difficult to study because of (a) the multidimensionality and chronicity of patients' needs, (b) the complexity of and the number of social and health-related services provided, (c) the isolation of care in individual homes, and (d) the lack of norms and standards on which to base judgments. A study was undertaken of the quality of care received by two client groups receiving home- and community-based services, in which some of these difficulties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The study also indicated the need for better data upon which to base policy decisions about problems such as lack of community resources for long term care; fragmentation and duplication of services; lack of support for the family caregiving system; and coordination between institutional and community-based acute and long term health services. Case management was studied in an evaluation of the quality of care in Kentucky's Home and Cornmunitybased waiver (Beaulieu, 1991). That study documented that activities not strictly defined as case management, such as aid supervisory visits, were being interpreted by agencies as "case management.…”
Section: Home Health Care Services Quarterlymentioning
confidence: 99%
“…The study also indicated the need for better data upon which to base policy decisions about problems such as lack of community resources for long term care; fragmentation and duplication of services; lack of support for the family caregiving system; and coordination between institutional and community-based acute and long term health services. Case management was studied in an evaluation of the quality of care in Kentucky's Home and Cornmunitybased waiver (Beaulieu, 1991). That study documented that activities not strictly defined as case management, such as aid supervisory visits, were being interpreted by agencies as "case management.…”
Section: Home Health Care Services Quarterlymentioning
confidence: 99%